Routledge Handbook of Genomics, Health and Society - Hilgartner, Stephen; Gibbon, Sahra; Prainsack, Barbara; Lamoreaux, Janelle (Routledge International Handbooks, 2018)
The Handbook provides an essential resource at the interface of Genomics, Health and Society, and forms a crucial research tool for both new students and established scholars across biomedicine and social sciences. Building from and extending the first Routledge Handbook of Genetics and Society, the book offers a comprehensive introduction to pivotal themes within the field, an overview of the current state of the art knowledge on genomics, science and society, and an outline of emerging areas of research. Key themes addressed include the way genomic based DNA technologies have become incorporated into diverse arenas of clinical practice and research whilst also extending beyond the clinic; the role of genomics in contemporary 'bioeconomies'; how challenges in the governance of medical genomics can both reconfigure and stabilise regulatory processes and jurisdictional boundaries; how questions of diversity and justice are situated across different national and transnational terrains of genomic research; and how genomics informs - and is shaped by - developments in fields such as epigenetics, synthetic biology, stem cell, microbial and animal model research. Presenting cutting edge research from leading social science scholars, the Handbook provides a unique and important contribution to the field. It brings a rich and varied cross disciplinary social science perspective that engages with both the history and contemporary context of genomics and 'post-genomics', and considers the now global and transnational terrain in which these developments are unfolding.